Collagenase Clostridium histolyticum in the management of Peyronie's disease: a review of the evidence. (June 2016) - Traore, Elizabeth J.; Wang, William; Yafi, Faysal A.; Hellstrom, Wayne J. G.
Objectives: Peyronie's disease (PD) is a connective tissue disorder resulting in the abnormal accumulation of scar or plaques in the tunica albuginea of the penis. The condition is characterized by two phases: an active, inflammatory phase, and a stable, chronic phase. Collagenase Clostridium histolyticum (CCH) was isolated in the mid-1900s and postulated as a potential pharmacologic strategy for breaking down the abnormal connective tissue plaques of PD. Prior to the introduction of CCH, a wide variety of treatment modalities for PD were used in clinical practice, including oral and topical medications, intralesional injections, electromotive drug administration, extracorporeal shockwave therapy, traction, and invasive surgery, all with variable results. This review aims to examine the known data surrounding the use of intralesional CCH injections in the treatment of PD. Methods: CCH is a recently US Food and Drug Administration approved pharmacologic treatment for PD. Clinical trials using intralesional CCH injection therapy for the treatment of PD were reviewed for clinical safety and efficacy of treatment. Results: Studies demonstrated that CCH treatment administered in multiple cycles led to significant benefit in both the psychological and physical aspects of PD. The strongest evidence for CCH's effectiveness was revealed in large, multicenter randomized controlled trials (Investigation for Maximal Peyronie's Reduction Efficacy and Safety Studies I and II) in which intralesional CCH was combined with manual modeling of the penis. Although adverse events from treatment are relatively common, the majority are mild to moderate in degree, including penile pain, swelling, and bruising, which all resolve spontaneously. Conclusion: Overall, evidence indicates that CCH is a valuable, effective, and safe minimally invasive treatment option for men with PD.